Fundamentos del Steam-H, como estrategia del modelo educativo aplicado en la formación de ingenieros - Sánchez Manosalvas, Olga Teresa; Martínez Armendáriz, Germán Fernando (Tierra Infinita, 2024)
The training of engineers demands the application of specific didactic strategies that allow the development of reflective critical thinking, product of exploration, investigation of concrete problems, which combine uncertainty and opportunities as part of creative and innovative thinking to propose answers to the needs and achievement of the SDGs in the local, regional and global context. Seen in this way, didactic strategies cannot be disarticulated from the curricular design in its different levels, and these in turn must be a fundamental part of the Educational Model adopted by the Institution, therefore, problem-based learning that leads to project-based learning is assumed as a fundamental strategy of the Contextual Ecological Educational Model, a path towards planetary sustainability of the Universidad Politécnica Estatal del Carchi in Ecuador, It is applied at the classroom level with an inter and multidisciplinary approach recognizing the unity of the human being, which is at the same time physical, biological, psychological, cultural, social and historical, and at the same time an integral part of a collective, so it is necessary to identify the fundamentals that guide the application of STEAM-H, so that learning and professional training is meaningful and relevant